(untitled) (Bangladesh Journal of Psychiatry, 2017)
Elderly people are increasing day by day both in developing and developed country due to development of new treatment, increased awareness of people and improved health facilities. This present study was conducted with the aim to identify behavioral problems according to severity of dementia. This descriptive cross sectional study was conducted in the Department of Psychiatry and Department of Neuro-medicine of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh and in National Institute of Mental Health (NIMH), Sher-E-Bangla Nagar, Dhaka, Bangladesh from September 2013 to March 2015. A total 150 patients were selected purposefully; severity of dementia was graded according to Mini Mental State Examination (MMSE) and another questionnaire was applied to detect behavioral problems of patients. In this study mild dementia was found as the most frequent (38%), followed by severe dementia (35.3%) and moderate dementia (26.7%). The results indicated that behavioral problem was more common in severe dementia. Behavioral problem was more common in severe dementia than in mild and moderate dementia. Among behavioral problems sleep disturbance and sexual disturbance were statistically significant This study provides information about pattern of behavioral problems among patients with dementia. Liaison approach with other discipline may improve quality of life of these patients treatable. Bang J Psychiatry Dec 2014; 28(2): 50-52